Influence of surface treatments on corrosion resistance properties of ultrafine grained titanium alloys for biomedical applications - Pérez, Diego (2019)
Titanium and its alloys are used as biomaterials because their excellent combination of high corrosion resistance, low modulus of elasticity and biocompatibility. However, titanium and its alloys cannot meet all the clinical requirements. In this sense, in order to improve the electrochemical and bioactive properties, this thesis aims to evaluate the effect of the severe plastic deformation as well as the surface modification treatments on the corrosion resistance and bioactivity of titanium alloys (α' + β) and (β). The titanium alloys, Ti13Nb13Zr (α' + β) and Ti35Nb7Zr5Ta (β), were deformed by the high-pressure torsion (HPT) method. Afterward, surface modification treatments, such as the anodization and chemical treatments, were carried out both in samples non-deformed and deformed by HPT. Finally, corrosion and bioactivity tests were performed in simulated body fluid (SBF). The tests were performed on samples with treated surfaces compared with non-treated surfaces in the deformed and undeformed conditions. The samples’ microstructures were analyzed by confocal laser microscopy (CLM), scanning electron microscopy (SEM) and X-ray diffraction (XRD). Hardness tests were also performed after the HPT process. On the other hand, surface modification treatments, and the formation of apatite in bioactivity assays were evaluated by scanning electron microscopy (SEM), with chemical analyzes carried out by dispersive energy spectroscopy (EDS) and phase identification by X-ray diffraction (XRD). In general, the corrosion resistance of the titanium alloys improved with the anodization treatment. Apatite deposits were observed on Ti13Nb13Zr alloy samples, in the conditions non-deformed and deformed by HPT. The Ti35Nb7Zr5Ta appears to have a lower apatite-formation ability compared to Ti13Nb13Zr.